Pemanfaataan Penggunaan Sistem Informasi Donasi Pada Panti Asuhan Berbasis Website Pada Panti Asuhan Putra Muhammadiyah Purwokerto - Ari Widiyanti; Eva Argarini Pratama - AMIK BSI Purwokerto (Universitas Bina Sarana Informatika, 2017)
Abstract - Web-based information systems of donors. Putra Muhammadiyah Orphanage is a social institution caring for and providing services to orphans and underprivileged children. Putra Muhammadiyah Orphanage in need of a web that can support and make it easy for prospective donors to find out information about the Orphanage Putra Muhammadiyah without having to come to the place, in addition to the web can also be introduced to the wider community. An analysis of how to build information systems donation web-based Orphanage Putra Muhammadiyah Purwokerto using system development method used is the development of systems Waterfall with system design using UML diagram that provides a description or a description of the design of models and systems in the form of descriptions and diagrams to illustrate thoroughly The result of the system in general and intended for general public will be more familiar with the Orphanage Putra Muhammadiyah Purwokerto and can obtain accurate information.A website-based information system is needed by social institutions such as orphanages to assist in disseminating information and to increase the number of donors. Panti Asuhan Putra Muhammadiyah is a social institution that cares and provides services to orphans and underprivileged children. Putra Muhammadiyah orphanage requires a web that can support and provide convenience for prospective donors to find out information about the Orphanage Putra Muhammadiyah without having to come directly to the place, in addition to the web can also introduce to the wider community. Analyzing how to build a web based donation information system at Putra Muhammadiyah Nursing Purwokerto using System development method used is Waterfall system development with system design using UML diagram giving description or description of model and system design in the form of description and diagram which can describe general and comprehensive system The results will be aimed at the wider community to get to know the Orphanage of Putra Muhammadiyah Purwokerto and to obtain accurate information.Keywords: System, Information, Donate, Waterfall, UML Abstrak - Web-based information systems required by social institutions such as orphanages to help spread the message and to increase the number of donors. Putra Muhammadiyah Orphanage is a social institution caring for and provide services to orphans and underprivileged children. Putra Muhammadiyah Orphanage in need of a web that can support and make it easy for prospective donors to find out information about the Orphanage Putra Muhammadiyah without having to come directly to the place, in addition to the web can also be introduced to the wider community. An analysis of how to build information systems donation web-based Orphanage Putra Muhammadiyah Purwokerto using system development method used is the development of systems Waterfall with system design using UML diagram that provides a description or a description of the design of models and systems in the form of descriptions and diagrams to illustrate menyeluruhHasilnya system in general and intended for general public will be more familiar with the Orphanage Putra Muhammadiyah Purwokerto and can obtain accurate information.Sistem informasi berbasis website dibutuhkan oleh lembaga-lembaga sosial seperti panti asuhan untuk membantu dalam menyebarkan informasi dan untuk menambah jumlah donatur. Panti Asuhan Putra Muhammadiyah adalah suatu lembaga sosial yang merawat dan memberikan pelayanan kepada anak-anak yatim dan anak-anak kurang mampu. Panti Asuhan Putra Muhammadiyah membutuhkan adanya suatu web yang dapat menunjang dan memberikan kemudahan bagi calon donatur untuk mengetahui informasi tentang Panti Asuhan Putra Muhammadiyah tanpa harus datang langsung ketempat, selain itu dengan adanya web juga dapat mengenalkan kepada masyarakat yang lebih luas. Penganalisaan tentang bagaimana cara membangun sistem informasi donasi berbasis web pada Panti Asuhan Putra Muhammadiyah Purwokerto dengan menggunakan Metode pengembangan sistem yang digunakan adalah pengembangan sistem Waterfall dengan perancangan sistem menggunakan diagram UML yang memberikan gambaran atau deskripsi perancangan model dan sistem dalam bentuk uraian dan diagram yang dapat menggambarkan sistem secara umum dan menyeluruhHasilnya akan ditujukan untuk masyarakat luas supaya lebih mengenal Panti Asuhan Putra Muhammadiyah Purwokerto serta dapat memperoleh informasi yang akurat. Kata kunci: Sistem, Informasi, Donasi, Waterfall, UML